Distributed Approach for Coverage and Patrolling Missions with a Team of Heterogeneous Aerial Robots under Communication Constraints. (10th January 2013) - Acevedo, Jose Joaquin; Arrue, Begoña C.; Maza, Ivan; Ollero, Anibal
Using aerial robots in area coverage applications is an emerging topic. These applications need a coverage path planning algorithm and a coordinated patrolling plan. This paper proposes a distributed approach to coordinate a team of heterogeneous UAVs cooperating efficiently in patrolling missions around irregular areas, with low communication ranges and memory storage requirements. Hence it can be used with small-scale UAVs with limited and different capabilities. The presented system uses a modular architecture and solves the problem by dividing the area between all the robots according to their capabilities. Each aerial robot performs a decomposition based algorithm to create covering paths and a 'one-to-one' coordination strategy to decide the path segment to patrol. The system is decentralized and fault-tolerant. It ensures a finite time to share information between all the robots and guarantees convergence to the desired steady state, based on the maximal minimum frequency criteria. A set of simulations with a team of quad-rotors is used to validate the approach.